Calibrating ultrasonic sensor measurements of crop canopy heights: a case study of maize and wheat - Zheng, Yudong; Hui, Xin; Cai, Dongyu; Shoukat, Muhammad Rizwan; Wang, Yunling; Wang, Zhongwei; Ma, Feng; Yan, Haijun (Frontiers in Plant Science, 2024)
Canopy height serves as an important dynamic indicator of crop growth in the decisionmaking process of field management. Ultrasonic sensors possess the ability to acquire crop height data through prolonged exposure in the field at an affordable price, offering the benefits of enhanced efficiency and convenient non-contact measurement, and their data is easy to process. However, the acoustic wave characteristics and crop canopy structure affect the measurement accuracy. To improve the ultrasonic sensor measurement accuracy, a four-year (2018−2021) field experiment was conducted on maize and wheat, and a measurement platform was developed. A series of single-factor experiments were conducted to investigate the significant factors affecting measurements, including the observation angle (0−60°), observation height (0.5−2.5 m), observation period (8:00−18:00), platform moving speed with respect to the crop (0−2.0 m min −1 ), planting density (0.2−1 time of standard planting density), and growth stage (maize from three−leaf to harvest period and wheat from regreening to maturity period). The results indicated that both the observation angle and planting density significantly affected the results of ultrasonic measurements (p-value < 0.05), whereas the effects of other factors on measurement accuracy were negligible (p-value > 0.05). Moreover, a double-input factor calibration model was constructed to assess canopy height under different years by utilizing the normalized difference vegetation index and ultrasonic measurements. The model was developed by employing the least-squares method, and ultrasonic measurement accuracy was significantly improved when integrating the measured value of canopy heights and the normalized difference vegetation index (NDVI). The accuracy of maize measurements varied between root mean squared error (RMSE) 81.4 and 93.6 mm, and the accuracy of wheat measurements was within the range of RMSE 37.1 to 47.2 mm. The research results can contribute to a more timely observation of crop growth status and field management decision-making based on ground-based agricultural machinery platforms.